Textual Authority and Exegetical Method in Salafi Tafsir: Reassessing Ibn Kathir in Contemporary Qur'anic Studies - Nasrullah, Iklil; Murtadho, Muhammad Alfa Choirul; Umami, Khoirul (Universitas Muhammadiyah Surakarta, 2026)
Contemporary Qur'anic studies have been increasingly shaped by contextual, literary, and hermeneutical approaches, yet relatively little attention has been given to how classical transmitted exegesis continues to function as a rigorous interpretive system in modern scholarship. While Ibn Kathīr is among the most widely referenced classical exegetes in the Muslim world, his tafsīr is often treated as a traditional authority rather than critically examined as a structured exegetical methodology with contemporary relevance. This article seeks to fill that gap by reassessing the textual authority and exegetical method of Salafī tafsīr through the interpretive framework of Ibn Kathīr. Using a qualitative library research design, this study analyzes primary classical sources, especially Tafsīr al-Qur'ān al-'Aẓīm, alongside modern scholarly discussions on Salafī exegesis, hadith-based interpretation, and contemporary Qur'anic thought. The analysis is conducted through descriptive, intertextual, and conceptual approaches to examine the epistemic hierarchy of Ibn Kathīr's method, including the use of intra-Qur'anic interpretation, Prophetic traditions, Companion reports, linguistic analysis, and critical engagement with Isrā'īliyyāt. The study finds that Ibn Kathīr's exegetical method is not merely a conservative reliance on transmitted materials, but a disciplined hermeneutical model that combines textual fidelity, source criticism, and interpretive coherence. His tafsīr reflects a structured balance between naqlī authority and controlled rational inquiry, making it especially relevant in the face of contemporary challenges such as interpretive subjectivism, decontextualized scriptural readings, and the rapid spread of unverified religious knowledge in digital environments. At the global level, this study contributes to contemporary Qur'anic studies by demonstrating that classical Salafī exegesis can still offer a productive methodological framework for discussions of textual authority, authenticity, and responsible interpretation. It also provides a critical intellectual resource for broader debates on religion, knowledge, and hermeneutics in an increasingly plural and digitized world.